ChemInform Abstract: Synthesis of Sulfonamides via I2‐Mediated Reaction of Sodium Sulfinates with Amines in an Aqueous Medium at Room Temperature. Issue 29 (July 2015) - Pan, Xiaojun; Gao, Jian; Liu, Juan; Lai, Junyi; Jiang, Huanfeng; Yuan, Gaoqing
Abstract Compared with previous studies, the introduced procedure has the advantages of simplicity, environmentally friendliness, and low costs.